The Ten Commandments: interpreting the Bible in the medieval world - Smith, Lesley (Studies in the history of Christian traditions, 2014)
Using the commentaries of a group of scholars from c. 1150-1350, along with confessors' manuals, mystery plays and sermon material, this book investigates the place of the Decalogue in medieval religious life and thought